Politik Kartel di Tingkat Lokal: Studi Pemilihan Wakil Gubernur Kepulauan Riau Periode Sisa 2016-2021 - Euis Ammelia; Meidi Kosandi (Indonesian Journal of Religion and Society, 2019)
This paper discusses the behavior of political party in Deputy Governor election (Pilwagub) at Riau Islands Province (Kepri) 2017 with rational choice and cartel politics approach. The DPRD of Riau Islands Provincial decision to to choose and assign Isdianto as Deputy Governor requires controversy, it is caused by the domination of one coalition over the other in the 2015 Governor election. This study argues that the motive for power in inter-party relations at the local level, especially those who have seats in Parliament of Riau Islands Province, tends to influence DPRD’s decision. Political parties effort at the local level through electoral changes are characterized by the pragmatism of political parties. The parties that competed in the 2015 Pilgub challenged reconciliation since the 2017 governor election. The findings of this study are those that discuss cartel policy through unseen agreements that are reflected in the DPRD's plenary decision by acclamation.